The Dictionary Properties of Verbs in the Definition of National-Cultural Units (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article investigates the optimal representation of verbs in bilingual dictionaries to accurately convey national-cultural realities. Verbs play a central role in expressing actions, rituals, and institutional behaviors, necessitating a lexicographical approach that includes valency, collocational patterns, and semantic prosody. Drawing on corpus-stylistic analysis and translation theory, the study proposes a structured microstructure for verb entries. Using the English-Karakalpak (ING-QQ) dictionary project as a case study, 15 culturally significant verbs are analyzed. The analysis culminates in seven methodological guidelines for verb entry compilation, emphasizing the importance of corpus data, register specification, and a balanced application of translation strategies like transposition, modulation, and equivalence to navigate domestication and foreignization.